Pertumbuhan Hortikultura di Lahan Bekas Tambang Timah, Bangka - NURTJAHYA, EDDY; MELLAWATI, JUNE; PRATAMA, DENI; RANI, RANI; HERAFI, CIATRI (Agrotrop : Journal on Agriculture Science; Vol 13 No 2 (2023), 2023)
The Growth of Horticultural Crops on Ex-Tin Mined Soil, Bangka . Growth evaluation of the plant parts consumed from various horticultural species is needed in an effort to determine adaptive economic plant species in ex-tin mined soil. This study aims to determine the growth of crops on ex-tin mined soil and on undisturbed soil in Bangka regency. Three individuals of each species were then measured for their root dry weight, horizontal root length, vertical root length, plant height, stem diameter, canopy width, shoot dry weight, and leaf thickness and leaf area. Plant growth on control land was higher than the growth on ex-tin mined soil for most of the parameters. It is suspected that this is due to the physical, chemical and biotic properties ex-tin mined soil properties which are not yet optimal for growth.